PENGARUH CELAH ELEKTRODE BUSI TERHADAP KINERJA MESIN HONDA GL 100 - Harjanto, Budi; Wijanarko, Heri; Sukahar (PPM Sdirjianbang Akademi Militer, 2025)
This study aims to analyze the effect of spark plug electrode gap variations on the performance of the Honda GL 100 105 cc engine at the PAL Akmil workshop. Combustion in a gasoline engine occurs in the combustion chamber due to the spark plug’s electrical discharge, which is influenced by the voltage difference between the central electrode and the ground electrode, as well as the electrode gap. A gap that is too small can hinder flame kernel development, leading to suboptimal combustion and reduced engine performance. The experiment was conducted using an NGK DE8A spark plug with electrode gap variations of 0.6 mm, 0.7 mm, and 0.8 mm, and engine speed variations ranging from 3000 to 9000 rpm, increasing by 1000 rpm, using a dynamometer. The results showed that the highest torque was obtained at a 0.8 mm gap at 6000 rpm, measuring 7.19 Nm, while the lowest torque was recorded at a 0.6 mm gap at 9000 rpm, measuring 4.63 Nm. The highest power output was achieved at a 0.6 mm gap at 8000 rpm, reaching 6.81 HP, while the lowest power was observed at a 0.6 mm gap at 3000 rpm, at 2.75 HP. The highest brake mean effective pressure (BMEP) was recorded at a 0.8 mm gap at 6000 rpm, measuring 1.15 kPa, whereas the lowest BMEP was observed at a 0.6 mm gap at 9000 rpm, at 0.74 kPa. The study concludes that spark plug electrode gap variations significantly affect engine performance, with the optimal gap for torque and BMEP found to be 0.8 mm.